EFFICIENCY OF THE PROGRAM FOR DESIGNING OF PEDAGOGICAL WORKERS’ INDIVIDUAL EDUCATIONAL TRAJECTORIES - Sukhenko, Yana (PSYCHOLOGICAL JOURNAL, 2020)
The article analyses of the results the implemented program for designing of pedagogical workers’ individual educational trajectories. During the performed experiment we observed changes in pedagogical workers’ body-intellectual, dynamic-motivational structures and in their personal potential in both, control and experimental groups. The changes demonstrated by the program participants were more dynamic and corresponded better to the external, situational context, namely, the reformation of general secondary schools in accordance with the “New Ukrainian School” program, which is “hybrid” and contradictory as for its content and procedures. As for the control group, the external, “background” conditions were manifested at all studied levels (dynamic-motivational, personal, self-evaluative), with the exception of the body-intellectual one; as for the experimental group, these conditions were manifested at all levels without exception. The synchronized unidirectional statistically significant changes in the control and experimental groups were determined for the following indicators: increased introjected, external motivation, deeper meaningfulness of life. The formative influence of the program was manifested by the strengthened positive dynamics of those tendencies that were outlined in the control group (the better ability to represent the educational trajectory), as well as by other changes, in particular: the strengthened innovative component of the educational trajectory, the tendency to devalue the result-conscious and emotional-evaluative components of educational experiences; developed general abilities and motivation; a tangible increase in the potential for self-determination against the background of the decreased potential for realization, in general, and reflexivity, in particular. Such dynamics of a personal potential corresponds to the classical ideas about behavior in transitional conditions: criticism, rational mechanisms fade into the background, pedagogical workers tend to rely on more spontaneous reactions, listen to themselves, self-determine and generate their own meanings and trajectories, or listen to those who can help and have the appropriate experience, finally, since the previous models / trajectories lose their relevance, do not work, do not satisfy new conditions, new ones begin to be developed.